The equity premium implied by production - Jermann, Urban J. (Journal of Financial Economics, 2010)
This paper studies the determinants of the equity premium as implied by producers’ first-order conditions. A simple closed form expression is presented for the Sharpe ratio as a function of investment volatility and technology parameters. Calibrated to the US postwar economy, the model can match the historical first and second moments of the market return and the risk-free interest rate. The model also generates a very volatile Sharpe ratio and market price of risk.